2020
DOI: 10.1093/nar/gkaa427
|View full text |Cite
|
Sign up to set email alerts
|

The conformational landscape of transcription intermediates involved in the regulation of the ZMP-sensing riboswitch from Thermosinus carboxydivorans

Abstract: Abstract Recently, prokaryotic riboswitches have been identified that regulate transcription in response to change of the concentration of secondary messengers. The ZMP (5-Aminoimidazole-4-carboxamide ribonucleotide (AICAR))-sensing riboswitch from Thermosinus carboxydivorans is a transcriptional ON-switch that is involved in purine and carbon-1 metabolic cycles. Its aptamer domain includes the pfl motif, which features a pseudoknot, impeding rho-independent term… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 44 publications
1
16
0
Order By: Relevance
“…1), suggesting that even partial termination hairpin folding competes with ligand binding. Consistent with a recent study on the Thermosinus carboxydivorans ZTP riboswitch 26 , these measurements suggest that, at equilibrium, there should exist an~10 nt ligand binding window. We labeled Δterm with donor (Cy3) and acceptor (Cy5) fluorophores 27 and tested for a ZMP-responsive conformational change using single-molecule FRET 28,29 (Fig.…”
Section: Resultssupporting
confidence: 88%
“…1), suggesting that even partial termination hairpin folding competes with ligand binding. Consistent with a recent study on the Thermosinus carboxydivorans ZTP riboswitch 26 , these measurements suggest that, at equilibrium, there should exist an~10 nt ligand binding window. We labeled Δterm with donor (Cy3) and acceptor (Cy5) fluorophores 27 and tested for a ZMP-responsive conformational change using single-molecule FRET 28,29 (Fig.…”
Section: Resultssupporting
confidence: 88%
“…As the F. ulcerans ZTP riboswitch is an ''ON'' switch, adding increasing ZMP to the transcription reaction stabilizes the aptamer fold of the RNA, prevents termination, and leads to the accumulation of the readthrough product (Figure 3B), which can be quantified and fit to determine the concentration at which the riboswitch is half activated (T 50 ). In these experiments, T 50 values are higher than K d values determined from other methods, as the riboswitch is kinetically controlled under these conditions (Binas et al, 2020;Strobel et al, 2019;Wickiser et al, 2005b). Thus, the T 50 values are non-equilibrium measurements that reflect ligand binding on rates (k on ).…”
Section: Aica Derivatives Bind and Activate Ztp Riboswitchesmentioning
confidence: 83%
“…Previous work with the Clostridium beijerinckii (Cbe) pfl ZTP riboswitch showed that this disruption of the AD in the absence of Z proceeds via a strand displacement mechanism (15), which has been supported by later smFRET and NMR studies of the Fusobacterium ulcerans and Thermosinus carboxydivorans ZTP riboswitches, respectively (13,30). Building off of this work, we used a functional mutagenesis approach with E. coli in vivo reporter assays to show that kinetic barriers to strand displacement can be used to tune ZTP riboswitch dynamic range.…”
Section: Introductionmentioning
confidence: 83%